The Reality Inside Nepal-India Open Border - BK, Upendra Bahadur (Journal of Management, 2025)
The article intends to explore the extent of age-old practices and integration of open border between Nepal and India besides the debates and security challenges brought by the open border regime. A natural practice of open border regime between Nepal and India has been facilitating social, cultural and economic exchanges. The objective of the study is to interpret the opportunities and threats of open border regime in the changed context based on the research questions ahead: Why is open border regime supported as well as debated? Following a secondary analysis of cooked information from the library and online sources as a research method, the study found that a misuse of open borders by terrorists, smugglers, anti-social elements and political activists has posed some challenges to the stakeholders leading to the demand of closure of the open border from Nepalese side. Nepal has been witnessing arguments for and against the open border in recent times to manage security and peace issues. The consolidated actions and policies are need of the hour to regulate the border for natural convenience of peace and security. Open border between Nepal and India remain instrumental to interdependence.